Influence Of Acidified Blanching Water And Pectinase Enzyme Treatments On Quality Of Carica Papaya Juice - Zaidi, Aina Nadiah (Universiti Sains Malaysia, 2020)
Papaya (Carica papaya) fruit ripen very fast which resulting post-harvest losses. There are various products made from papaya including papaya juice. However, high pectin content in papaya makes the juice extraction become complicated and produced a very viscous and concentrates papaya juice. Therefore, this study aims to determine the effect of acidified blanching water and pectinase enzyme on physicochemical properties, antioxidant activities and consumer acceptability of Carica papaya juice. The papaya was treated with different concentration of citric acid (1.5% and 2.5%) blanching water and combination of citric acid blanching water with different concentration pectinase enzyme (0.05% and 0.10%). Determination of physicochemical properties (yield, pH, colour, total soluble solids (TSS)), antioxidant (total phenolic content (TPC), DPPH assay and ascorbic acid) and consumer acceptability (hedonic test and food action rating scale (FACT) test) were carried out. Result showed that, application of acidified blanching water and pectinase enzyme of treatments, had no significant different (p>0.05) effect on the percentage of the papaya juice yield. The combination of 1.5% citric acid blanching water with 0.05% pectinase enzyme treatment was effective (p<0.05) to degrade the pectin and reduce the viscosity and produce high clarity of papaya juice.